1976
DOI: 10.1021/ja00436a045
|View full text |Cite
|
Sign up to set email alerts
|

Tautomerism in cytosine and 3-methylcytosine. A thermodynamic and kinetic study

Abstract: Aqueous cytosine, which exists mainly as the 1 (//)-aminooxo form (la), is shown by temperature-jump spectroscopy to tautomerize slightly to the 3(//)-aminooxo form (Ila); the equilibrium constant K = (IIa)/(Ia) is estimated to be (2.5 ± 0.5) X 10-3 at 25 °C and the tautomerization enthalpy is 3.1 ± 0.1 kcal M_1. At 10 °C, The interconversion process is catalyzed by water [kH2o = (1.8 ± 0.3) X 103 s~1 ], by H+ [kH+ = (1.6 ± 0.3) X 1010M-' s-'],by OH" [fc0H-= (1.2 ±0.05) X 1010 M_1 s_1], and by the cytosinium c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

11
115
0
1

Year Published

1978
1978
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(127 citation statements)
references
References 5 publications
11
115
0
1
Order By: Relevance
“…These findings are in contrast to cytosine in aqueous solution, where the canonical keto form is calculated to be much more stable than other tautomers 12,19 and only this form is likely to contribute to the experimental spectrum. 20,21 Recently, Kosma et al 7 observed appreciable dependence of decay profiles on the excitation wavelength in the femtosecond time-resolved pump-probe ionization spectroscopy of isolated cytosine, and attributed this remarkable observation to the coexistence of the keto, imino, and enol tautomers. With the excitation wavelengths of 290, 280, 270, and 267 nm, the observed transients were decomposed into three components with lifetimes of τ 1 < 0.25 ps, τ 2 = 1.1 − 2.3 ps, and τ 3 ≥ 19 ps.…”
Section: Introductionmentioning
confidence: 99%
“…These findings are in contrast to cytosine in aqueous solution, where the canonical keto form is calculated to be much more stable than other tautomers 12,19 and only this form is likely to contribute to the experimental spectrum. 20,21 Recently, Kosma et al 7 observed appreciable dependence of decay profiles on the excitation wavelength in the femtosecond time-resolved pump-probe ionization spectroscopy of isolated cytosine, and attributed this remarkable observation to the coexistence of the keto, imino, and enol tautomers. With the excitation wavelengths of 290, 280, 270, and 267 nm, the observed transients were decomposed into three components with lifetimes of τ 1 < 0.25 ps, τ 2 = 1.1 − 2.3 ps, and τ 3 ≥ 19 ps.…”
Section: Introductionmentioning
confidence: 99%
“…But evidence for these types of tautomeric shifts remains sparse, because the limited sensitivity of the experimental methods prevents an accurate detection of the relative amount of the rare tautomers including mutagenic. Among all rare tautomers, only the imino tautomers of Cyt (Brown et al, 1989b;Dreyfus et al, 1976;Feyer et al, 2010;Szczesniak et al, 1988) and enol tautomers of Gua (Choi & Miller, 2006;Sheina et al, 1987;Plekan et al, 2009;Szczepaniak & Szczesniak, 1987) were experimentally detected. The lack of the experimental data on the rare tautomers of Ade (Brown et al, 1989a) and Thy can be explained by the high value of their relative energy (~12÷14 kcal/mol at 298.15 K) estimated by theoretical investigations (Basu et al, 2005;Brovarets' & Hovorun, 2010a;Fonseca Guerra et al, 2006;Mejía-Mazariegos & Hernández-Trujillo, 2009;Samijlenko et al, 2000Samijlenko et al, , 2004.…”
Section: Introductionmentioning
confidence: 99%
“…The five nucleic acid bases, cytosine, thymine, uracil, adenine, and guanine, found in DNA and RNA control the replication of DNA, store information required to synthesize proteins, and translate this information to the protein. Tautomerism is a well-known phenomenon occurring in nucleic acid bases [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16], in which proton transfer from the heterocyclic ring center to an exocyclic oxo-or imino-group leads to the formation of either an -OH or an -NH 2 groups. These processes are known as keto-enol or imino-amino tautomerism, respectively.…”
Section: Introductionmentioning
confidence: 99%